A new nonexercise-based [latin capital V with dot above]O2max equation for aerobically trained females - Malek, M. H.; Housh, T. J.; Berger, D. E.; Coburn, J. W.; Beck, T. W. (Medicine & Science in Sports & Exercise, 2004)
Purpose: The purposes of the present study were to (a) modify previously published [latin capital V with dot above]O2max equations using the constant error (CE) values for aerobically trained females, (b) cross-validate the modified equations to determine their accuracy for estimating [latin capital V with dot above]O2max in aerobically trained females, (c) derive a new nonexercise-based equation for estimating [latin capital V with dot above]O2max in aerobically trained females if the modified equations are found to be inaccurate, and (d) cross-validate the new [latin capital V with dot above]O2max equation using the PRESS statistic and an independent sample of aerobically trained females. Methods: A total of 115 aerobically trained females (mean +/- SD: age = 38.5 +/- 9.4 yr) performed a maximal incremental test on a cycle ergometer to determine actual [latin capital V with dot above]O2max. The predicted [latin capital V with dot above]O2max values from nine published equations were compared with actual [latin capital V with dot above]O2max by examining the CE, standard error of estimate (SEE), validity coefficient (r), and total error (TE). Results: Cross-validation of the modified nonexercise-based equations on a random subsample of 50 subjects resulted in a %TE >= 13% of the mean of actual [latin capital V with dot above]O2max. Therefore, the following nonexercise-based [latin capital V with dot above]O2max equation was derived on a random subsample of 80 subjects: [latin capital V with dot above]O2max (mL[middle dot]min-1) = 18.528 (weight in kg) + 11.993 (height in cm) - 17.197(age in yr) + 23.522 (h[middle dot]wk-1 of training) + 62.118 (intensity of training using the Borg 6-20) + 278.262 (natural log of years of training) - 1375.878 (R = 0.83, R2 adjusted = 0.67, and SEE = 259 mL[middle dot]min-1). Cross-validation of this equation on the remaining sample of 35 subjects resulted in a %TE of 10%. Conclusions: The nonexercise equation presented here is recommended over previously published equations for estimating [latin capital V with dot above]O2max in aerobically trained females.